TWO-PHASE FRICTION FACTOR OBTAINED FROM VARIOUS VOID FRACTION MODELS DURING CONDENSATION OF R134A IN VERTICAL DOWNWARD FLOW AT HIGH MASS FLUX - Dalkilic, Ahmet Selim; Laohalertdecha, Suriyan; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2009)
Void fractions are determined in vertical downward annular two-phase flow of R134a inside 8.1 mm i.d. smooth tube. The experiments are done at average saturated condensing temperatures of 40 and 50 degrees C. The average qualities are between 0.84 - 0.94. The mass fluxes are around 515 kg m(-2)s(-1). The experimental setup is explained elaborately. Comparisons between the void traction determined from 35 void fraction correlations are done. According to the use of various horizontal and vertical annular flow void fraction models together with the present experimental condensation heat transfer data, similar void fraction results were obtained mostly for the smooth tube. The experimental friction factors obtained from void fraction correlations are compared with the friction factors determined from graphical information provided by Bergelin et. al. Effect of void fraction alteration on the momentum pressure drop is also presented.
Keywords: PRESSURE-DROP; HEAT-TRANSFER; PREDICTION; GAS; Thermodynamics; Engineering; Physics